A Phonological Structure of Dual and Salāmah Plural: Contemporary Linguistic Description For Non-Arabic Learners/ التشكيل الصوتيّ للمثنَّى وجموع السلامة: وصف لسانيّ معاصر لمتعلِّمي العربيّة من الناطقين بغيرها - Mohd Nizwan Musling (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Nowadays, Arabic language pedagogy has improved its content to align with the updated and revised global knowledge. However, most Arabic language morphology books learned and used by non-native speakers are designated based on conventional information. The content relies mainly on discussing Arabic words' physical characteristics rather than acoustic characteristics. For instance, some contemporary Arabic linguists have not revised how phonics is formed, for example, the dual and Salamah plural structure. On that note, this study investigates the phonological rules and their explanation of how the dual and salāmah plurals are formed, which can be beneficial in teaching Arabic morphology. The study utilizes the descriptive analytical approach by identifying all types of dual and salāmah plural in the Arabic language and analyses based on the phonological framework using international linguistics transliteration symbols. One of the most important findings of the study is that the vocal structure of dual and salāmah plural is formed by adding suffix in the single last word, namely for dual: āni, and, and for salāmah plural: ūna, īna, ātu, and āti. The most critical phonological rules that formed these structures are the Arabic language's dissimilation and the syllable system. The benefits of this study for teaching Arabic are to facilitate morphological descriptions for non-native Arabic learners and present an accurate analysis using symbols and phonological rules, which is more significant to comprehend the nature of human language based on modern scientific thinking.